Neuroart: picturing the neuroscience of intentional actions in art and science - Siler, Todd (Frontiers in Human Neuroscience, 2015)
Intentional actions cover a broad spectrum of human behaviors involving consciousness, creativity, innovative thinking, problem-solving, critical thinking, and other related cognitive processes self-evident in the arts and sciences. The author discusses the brain activity associated with action intentions, connecting this activity with the creative process. Focusing on one seminal artwork created and exhibited over a period of three decades, Thought Assemblies (1979-82, 2014), he describes how this symbolic art interprets the neuropsychological processes of intuition and analytical reasoning. It explores numerous basic questions concerning observed interactions between artistic and scientific inquiries, conceptions, perceptions, and representations connecting mind and nature. Pointing to some key neural mechanisms responsible for forming and implementing intentions, he considers why and how we create, discover, invent, and innovate. He suggests ways metaphorical thinking and symbolic modeling can help integrate the neuroscience of intentional actions with the neuroscience of creativity, art and neuroaesthetics.